LAW ENFORCEMENT AGAINST SELLERS OF NON-CUSTOM GOODS (THRIFT CLOTHES) IN PALANGKA RAYA CITY - Yosa Nikolas Notoe Saleh; Andika Wijaya; Putri Fransiska Purnama P; Satriya Nugraha (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to identify and analyze law enforcement against sellers of non-excise goods in the form of illegal imported thrift clothing in Palangka Raya City, as well as the obstacles faced by the Customs and Excise Office and the Department of Trade and Industry in its implementation. This research is motivated by the widespread circulation of imported thrift clothing that does not go through official customs procedures, thereby violating applicable legal provisions, particularly Law Number 17 of 2006 concerning Customs and Ministry of Trade Regulation Number 40 of 2022 concerning the prohibition of imported used clothing. The research method used is empirical juridical legal research supported by a normative juridical approach. Data were collected through interviews, field observations, and literature studies related to laws and regulations, journals, and other legal references. The research locations included thrift shops in Kilometer 7, Palangka Raya City, as well as related institutions such as the Customs and Excise Office and the Department of Trade and Industry of Palangka Raya City. The results of the study indicate that law enforcement against sellers of illegal imported thrift clothing in Palangka Raya City has not been implemented optimally. This is caused by a lack of supervision, limited personnel and supporting facilities, low public legal awareness, and the high public interest in imported thrift clothing due to its relatively affordable prices and perceived quality. In addition, coordination among related institutions in supervision and enforcement still needs improvement in order to achieve more effective law enforcement. Based on these findings, it is necessary to strengthen supervision over the circulation of illegal imported goods, improve inter-agency coordination, and conduct public socialization regarding legal regulations and the risks of using illegal imported goods in order to create legal certainty and public protection.